Efficiency and Creativity in The Creative Industry Through the Utilization of Machine Learning (Case Study at CV. Maxiidea Arta Sukses, Surabaya) - Satria, Brama Seta Putra; Fadhillah, Is (International Journal Software Engineering and Computer Science (IJSECS), 2023)
The creative industry in Indonesia is a key contributor to economic growth, and technology, particularly Machine Learning, is playing a crucial role in its transformation. This research focuses on the impact of Machine Learning implementation in the creative industry, specifically at CV. Maxiidea Arta Sukses in Surabaya, and aims to understand its effects on efficiency and creativity. By using qualitative methods such as observation, interviews, and literature study, the research examines the improvements in efficiency for social media specialists, the impact on creativity in digital marketing, and the potential barriers to implementation. The findings provide valuable insights into employee perceptions of Machine Learning technology and its potential contribution to performance. Ultimately, this research sheds light on the evolving role of technology in the creative industry and its implications for businesses in Indonesia.